Food security reduces multiple HIV infection risks for high-vulnerability adolescent mothers and non-mothers in South Africa: a cross-sectional study - Cluver, L; Rudgard, WE; Toska, E; Orkin, M; Ibrahim, M; Langwenya, N; Kuo, C; Xaba, N; Roehm, K; Smith, M; Bernardini, S; Giordana, G; et al. (Wiley, 2022)
Introduction Adolescent girls and young women, including adolescent mothers, in Southern Africa have high HIV seroconversion and transmission. We need to know which risks drive HIV infections, and what can reduce these risks.